Cloning of a Recombinant Plasmid Encoding PpSP42 Protein Fragment of Phlebotomus papatasi and expressing it in HEK-293T Eukaryotic Cell - Touraj MIANDOABI; Fariborz BAHRAMI; Vahideh MOEIN VAZIRI; Soheila AJDARY (Tehran University of Medical Sciences, 2019)
No Abstract####